Simulation Study of Stochastic Wind Field of Catenaries with Spatial Correlativity - 曹树森; 秦剑; 柯坚; 刘晓红 (机车电传动)
According to catenary construction, at unreduced precision, a multivariable simulation model of catenary stochastic pulsation wind field based on the harmonic synthesis was proposed, which properly simplifies wind speed coherence function and power spectral density function. The simulation model adopted the Davenport power spectral density unchanging along the height and considered the correlations between three turbulent wind components at different points and introduced the discrepancy at different phase angles to represent the time delay in wind velocity passage. The FFT technique (fast Fourier transform technique) is used to enhance the harmonic synthesis efficiency. A numerical example of simulation for stochastic wind field of the hundred-mile wind field at Lanchow-Sinkiang railway is included in this paper to illustrate the improved method introduced. It is demonstrated that the cross-power spectral density function and cross-correlation function are in good agreement with the expected targets. It means that the proposed method can simulate the target stochastic pulsing wind velocity field accurately and effectively.